CONTRIBUTION OF BABURIAN DYNASTY TO WORLD CIVILIZATION: https://doi.org/10.5281/zenodo.13852532 - Toshkhojayev , Shokhrukh (Journal of Contemporary World Studies, 2024)
The article talks about the place of the great poet and statesman Zahiruddin Muhammad Babur in the world civilization, his unique qualities, life principles and philanthropic activities. Babur's humanitarian ideas are illuminated by his creative work in India, his contribution to the development of the country and his services in bringing the oriental culture.